Analisis Pada Cerpen “Mata Yang Indah” Karya Budi Darma - Agnan Masykuri; Aysilla Afifah Baehaki (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
The short story "Mata yang Indah" by Budi Darma explores themes of guilt, and the human quest for redemption. This analysis examines the narrative structure, character development, and the symbolic significance of the "beautiful eyes" motif. Using a qualitative approach, this study finds that the story employs a complex interplay of memory and reality to evoke existential questions about human frailty and divine judgment. The findings contribute to understanding Indonesian literary narratives in exploring moral and spiritual conflicts. Keywords: Short story analysis, Indonesian literature, morality, symbolism, Budi Darma